Pemanfaatan Digital Marketing dalam Mempromosikan Destinasi Pariwisata - I Putu David Adi Saputra (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This study aims to analyze the use of Digital Marketing in Promoting Tourism Destinations. This research is a literature review. Data collection techniques are documentation from journal sources and relevant literature such as Google Scholar. Data analysis with critical literature. research results The use of digital marketing in promoting tourism destinations has become the key to success in this modern era. Through digital platforms such as social media, websites and online advertising campaigns, tourism destinations can effectively reach and interact with global audiences in real-time. Digital marketing strategies enable tourism destinations to showcase the beauty of nature, culture and facilities offered through attractive visual content, story-based content and visitor testimonials. In addition, content personalization and precise targeting enable tourism destinations to create unique experiences for potential travelers, while data analysis and online feedback provide valuable insights to improve the services and attractiveness of these destinations. Thus, the use of digital marketing not only increases the visibility of tourism destinations, but also plays an important role in inspiring, informing and captivating a global audience to explore the beauty the world has to offer.